(untitled) (Ciencias Veterinarias, 2015)
Several common causes of trauma on the thoracolumbar spine of the horse are discussed. In addition, some pathologies affecting the vertebral dorsal spinous processes and saddle related problems are mentioned. Since these aspects are sources of pain, the authors consider that this topic should also be approached from the animal welfare perspective.